2020
DOI: 10.1089/sur.2019.203
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Practice and Comparison with Best Evidence in Surgical Site Infection Prevention in Colorectal Surgery

Abstract: Background: The use of mechanical bowel preparation and prophylaxis with oral antimicrobial agents can prevent surgical site infection (SSI) in colorectal surgical procedures, but routine adoption of these and other practices by surgeons has been limited. The aim of this study was to determine the actual practice and surgeon beliefs about preventative measures in elective colorectal operations and to compare them with established recommendations. Methods: Web-based survey was sent to colorectal surgeons assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Despite these huge amounts of several different studies, many centers seemed to stay conservative and conformist, which may be failed to enhance the optimal level of skin preparation [9][10][11]. Our study demonstrated not only the different techniques of skin antisepsis but also a very significant attempt to digress the comfort zone of conventional disinfection techniques.…”
Section: Discussionmentioning
confidence: 78%
“…Despite these huge amounts of several different studies, many centers seemed to stay conservative and conformist, which may be failed to enhance the optimal level of skin preparation [9][10][11]. Our study demonstrated not only the different techniques of skin antisepsis but also a very significant attempt to digress the comfort zone of conventional disinfection techniques.…”
Section: Discussionmentioning
confidence: 78%
“…Historically, mechanical cleansing was thought to be among the most important factors influencing outcomes in colorectal surgery 105 . Today, the use of preoperative MBP is still commonly practiced 100 , 106 , 107 and widely recommended 35 . The current study found no clear advantage from the addition of MBP, which contrasts with results of several previous studies, including previous large retrospective cohort studies of the ACS NSQIP colectomy database 31–33 , 108 , which favoured combined MBP + OAB.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Health careassociated infections (HCAIs) was 7.59 percent and 14.5% of this infection was associated with SSIs in study done among 75,694 patients in Republic of Ireland, England, Wales and Northern Ireland, SSIs are among the most preventable HCAIs, according to the World Health Organization and the Centers for Disease Control and Prevention (CDC) [5]. In Europe SSIs prevalence 21.6% that's mean SSIs become now the most common hospital-acquired infection [6]. In 2017, research has been conducted on reducing surgical site infection with negative therapy and the result has shown 71 patients, comprising 33 in an Experimental Group and 38 in the Control Group, were included in this study between May 2014 and December 2015.…”
Section: Introductionmentioning
confidence: 99%